Determination of leaf area in guarana tree. I. Composite leaves - Reis, Geraldo Gonçalves dos; Regazzi, Adair José (Pesquisa Agropecuaria Brasileira, 2014)
The leaf area of guarana tree (Paullinia cupana var. sorbillis (Mart.) Ducke was evaluated from sixty healthy and complete growth leaves. The folioles were identified in five positions of the adaxial surface of the leaf: the first at right. A; the first as left, B; the second at right. C; the second at left, D and E, the remaining one. Several models of regression were tested to estimate the area of the all composite leaf as a function of the length (C). width (L), and of the product C.L. CX) from each foliole. Based on values presented by determination coefficient and significance of the parameters responsible by the Student “t" test. adopting 5% as a acceptable level of probability it was selected the modal: LogYi = 1.164421 + 0.409381 ** LogCi + 1.155910 ** LogLi, where length (Ci) and width (Li) correspond the dimensions of the foliole in the D position, and Yi correspond the estimated area of composite leaf.
Keywords: leaf area; guarana tree; Paullinia cupana var. sorbillis (Mart.) Ducke